Concrete with treated surface and exposed to chlorides solution: thickness of equivalent coatings - Medeiros, M. H. F.; Real, L. V.; Quarcioni, V. A.; Helene, P. (Revista ALCONPAT, 2015)
The main purpose of the experimental tests was to obtain the chloride diffusion coefficient and generate a chloride ingress prediction for surface treated concrete that could be valid during the initiation stage and transport by ions diffusion. The prediction was based on non steady-state conditions and some of the results indicated that a concrete with this type of protection can extend the chloride ingress up to three times. Data showed in this work indicated the equivalent cover of the surface treatment, ranging between 0.3 and 3.4 cm, showing large variations in results among the surface treatment materiais tested.Keywords: reinforced concrete, marine environment, chloride migration, service life.